Thromboprophylaxis prescribing among junior doctors: the impact of educational interventions. Issue 1 (December 2016) - Watt, Bethany; Williams, Dean; Lewis, Lauren; Whitaker, Christopher
Abstract Background Venous thromboembolism (VTE) prophylaxis in an important aspect of the care of hospitalised patients, for which the National Institute for Health and Care Excellence (NICE) has issued guidance. Guidance compliance continues to be a concern. Junior doctors are the main group responsible for prescribing thromboprophylaxis. We aimed to compare local pharmacological thromboprophylaxis prescribing against NICE guidelines in a surgical department at a district general hospital, and determine whether interventions aimed at improving compliance were effective. Methods Over four months, a two cycle audit of prescribing patterns for VTE prophylaxis was performed using data collected at four intervals: 1. Baseline 2. Following pro-forma introduction and feedback 3. A second baseline data collection. 4. Following VTE prophylaxis teaching. Results A total of 394 admissions were included. Correct identification and prescribing for at-risk patients ranged between 76 and 93 %, whilst risk assessment documentation and explanation to patients occurred in fewer than 50 and 66 % respectively. Prescribing and risk assessment improved in the first cycle (chi2 = 6.75, p = 0.009 and chi2 = 10.70, p = 0.001 respectively), a consequence of one specialty improving following additional feedback. Teaching was not associated with improvements. Overall compliance with NICE guidelines was achieved in no more than 25 % of admissions. Conclusions Despite junior doctors generally prescribing VTE thromboprophylaxis appropriately, overall compliance with guidelines remained poor regardless of educational interventions. Verbal feedback was the only intervention associated with modest improvements. A pressurised work environment may limit the impact of educational interventions. Guidance simplification or devolving responsibility to other members of staff may improve compliance.